2012
DOI: 10.1103/physrevc.86.014902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of results from a (2+1)-D relativistic viscous hydrodynamic model to elliptic and hexadecapole flow of charged hadrons measured in Au-Au collisions atsNN=200GeV

Abstract: Simulated results from a 2+1D relativistic viscous hydrodynamic model have been compared to the experimental data on the centrality dependence of invariant yield, elliptic flow (v2), and hexadecapole flow (v4) as a function of transverse momentum (pT ) of charged hadrons in Au-Au collisions at √ sNN = 200 GeV. Results from two types of initial transverse energy density profile, one based on the Glauber model and other based on Color-Glass-Condensate (CGC) are presented. We observe no difference in the simulate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…However, it has recently come to be appreciated that, in non-central ("peripheral") collisions, the QGP is also subjected to an extremely intense shearing motion, because of the transverse non-uniformity of the colliding nuclei [11][12][13]. The large vorticity thus generated [14][15][16][17][18] may prove to have observable consequences, through quark polarization, and it may be important for forthcoming attempts to simulate peripheral collisions using holography [19].…”
Section: Holographic Description Of the Internal Motion Of The Qgpmentioning
confidence: 99%
“…However, it has recently come to be appreciated that, in non-central ("peripheral") collisions, the QGP is also subjected to an extremely intense shearing motion, because of the transverse non-uniformity of the colliding nuclei [11][12][13]. The large vorticity thus generated [14][15][16][17][18] may prove to have observable consequences, through quark polarization, and it may be important for forthcoming attempts to simulate peripheral collisions using holography [19].…”
Section: Holographic Description Of the Internal Motion Of The Qgpmentioning
confidence: 99%
“…To explain the elliptic flow parameter v 2 extracted from data collected at the Relativistic Heavy Ion Collider (RHIC) [1][2][3][4][5][6][7], hydrodynamical calculations [8][9][10][11][12] as well as some transport calculations [13][14][15][16] suggest that the matter produced in the collisions is likely to have a very small ratio of shear viscosity to entropy density η/s. Recent studies [17][18][19][20][21][22] have shown that η/s may reach a minimum in the vicinity of a phase transition-for earlier studies, see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…One can use a Gaussian distribution for ( ). Transverse energy distribution ( , ) can be conveniently parameterised in a Glauber model [17] or in color glass condensate (CGC) model [46][47][48]. I briefly discuss the Glauber and CGC initial conditions.…”
Section: Initial Conditionmentioning
confidence: 99%
“…In Figure 9, viscous hydrodynamic simulation results [48] for transverse momentum spectra in √ = 200 GeV Au+Au collisions are compared with the PHENIX experiment. Glauber model initial condition was used for these simulations.…”
Section: Hydrodynamic Simulation Of Heavy Ion Collisions and Comparismentioning
confidence: 99%